Swan Song Swan song - Hilderbrand, Elin (New York : Little Brown, 2024)
"Chief of Police Ed Kapenash is about to retire. Blond Sharon is going through a divorce. But when a 22-million- dollar summer home is purchased by the mysterious Richardsons--how did they make their money, exactly?--Ed, Sharon, and everyone in the community are swept up in high drama. The Richardsons throw lavish parties, flirt with multiple locals, flaunt their wealth with not one but two yachts, and raise impossible hopes of everyone they meet. When their house burns to the ground and their most essential employee goes missing, the entire island is up in arms. The last of Elin Hilderbrands bestselling Nantucket novels, Swan Song is a propulsive medley of glittering gatherings, sun-soaked drama, wisdom and heart, featuring the return of some of her most beloved characters, including, most importantly, the beautiful and timeless island of Nantucket itself." --
Keywords: Friendship -- Fiction; Families -- Fiction; Marriage -- Fiction; Missing persons -- Fiction; Rich people -- Fiction; Neighbors -- Fiction; Communities -- Fiction; Islands -- Fiction; Nantucket Island (Mass.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Domestic fiction; Romance fiction